Blockchain‐based access control for enterprise blockchain applications. Issue 5 (23rd December 2019) - Xu, Lei; Markus, Isaac; I, Subhod; Nayab, Nikhil
Summary: Access control is one of the fundamental security mechanisms of IT systems. Most existing access control schemes rely on a centralized party to manage and enforce access control policies. As blockchain technologies, especially permissioned networks, find more applicability beyond cryptocurrencies in enterprise solutions, it is expected that the security requirements will increase. Therefore, it is necessary to develop an access control system that works in a decentralized environment without compromising the unique features of a blockchain. A straightforward method to support access control is to deploy a firewall in front of the enterprise blockchain application. However, this approach does not take advantage of the desirable features of blockchain. In order to address these concerns, we propose a novel blockchain‐based access control scheme, which keeps the decentralization feature for access control–related operations. The newly proposed system also provides the capability to protect user's privacy by leveraging ring signature. We implement a prototype of the scheme using Hyperledger Fabric and assess its performance to show that it is practical for real‐world applications. Abstract : We propose a novel blockchain‐based access control scheme, which keeps the decentralization feature for access control–related operations. The newly proposed system also provides the capability to protect user's privacy by leveraging ring signature.